2022
DOI: 10.1128/mbio.00300-22
|View full text |Cite
|
Sign up to set email alerts
|

A Poxvirus Decapping Enzyme Colocalizes with Mitochondria To Regulate RNA Metabolism and Translation and Promote Viral Replication

Abstract: Decapping enzymes comprise many members from various organisms, ranging from plants, animals, and viruses. The mechanisms regulating their functions vary and are still largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…20,21,24,34,35 D9 has been found to be nonessential for viral replication in cultured cells, but deletion of D10 results in smaller plaque size and a reduction in replication. 23 This correlates with our observation of early gene expression having little effect on inducing host shutoff, (Figure 3) as D9 is an early viral gene and D10 is an intermediate gene expressed post-DNA replication where we see greater host shutoff. 20,45,46 This would suggest that the post-replicative gene D10 plays a more critical role than D9 to induce host shutoff.…”
Section: Vacv With Inactive/deleted Decapping Enzymes Retains the Abi...supporting
confidence: 88%
See 3 more Smart Citations
“…20,21,24,34,35 D9 has been found to be nonessential for viral replication in cultured cells, but deletion of D10 results in smaller plaque size and a reduction in replication. 23 This correlates with our observation of early gene expression having little effect on inducing host shutoff, (Figure 3) as D9 is an early viral gene and D10 is an intermediate gene expressed post-DNA replication where we see greater host shutoff. 20,45,46 This would suggest that the post-replicative gene D10 plays a more critical role than D9 to induce host shutoff.…”
Section: Vacv With Inactive/deleted Decapping Enzymes Retains the Abi...supporting
confidence: 88%
“…VACV‐encoded decapping enzymes (D9 and D10) that cause accelerated mRNA degradation are the most well‐studied VACV host shutoff factors 20,21,24,34,35 . D9 has been found to be nonessential for viral replication in cultured cells, but deletion of D10 results in smaller plaque size and a reduction in replication 23 . This correlates with our observation of early gene expression having little effect on inducing host shutoff, (Figure 3) as D9 is an early viral gene and D10 is an intermediate gene expressed post‐DNA replication where we see greater host shutoff 20,45,46 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since that initial study, the VACV decapping enzymes D9 and D10 have each been shown to inhibit both PKR and RNase L activity. These enzymes act in concert with the host exoribonuclease Xrn1 to deplete both host and viral RNA, thereby reducing total intracellular dsRNA 22,[46][47][48] . However, as with rhtrs1, we did not detect any mutations in either of these VACV genes.…”
Section: Discussionmentioning
confidence: 99%